(untitled) (Research, Society and Development, 2022)
In general, credit risk is due to failure or default. The guarantee will ease the creditor to supervise the debtor for his debt and also minimize the occurrence of problems in the future. The finish of bad credit by creditors still has many obstacles because the binding using SKMHT (Power of Attorney to Impose Mortgages Right) has not been upgraded to the binding of APHT (Deed of Granting of Mortgage). This results in settlements through legal wat that can’t be carried out by the bank. This research aims to provide an alternative settlement of bad credit through a Simple lawsuit. This type of research is normative legal research. The data collection method was in the form of library data by collecting primary legal materials, such as legislation, and secondary legal materials, such as literature, books, and documents. The characteristics of this research were prescriptive research. In the process of resolving non-performing loans through litigation, it was only carried out when non-litigation efforts have been unable to provide a solution. This was due to the nature and function of the Power of Attorney to Impose Mortgages Right (SKMHT) only as a power of attorney to provide the Deed of Granting of Mortgage (APHT). It was not allowed to contain other legal actions other than those described in Article 15 of the Mortgage Law. Simple lawsuit is a mechanism for resolving cases quickly. examined is a simple case with a material claim value of at most 500 million that can be settled with a simple lawsuit following PERMA Number 4 of 2019.